The Role Of Media Literacy In The Image Of A Modern Teacher (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses media literacy, which encompasses skills and competencies for receiving and evaluating mass media content, in the context of the rapid development of information and communication technologies